FRI0224 Comparison of Efficacy and Safety of Rituximab Biosimilar, BCD-020, and Innovator Rituximab in Patients with Active Rheumatoid Arthritis Refractory To TNFA Inhibitors. (15th July 2016) - Eremeeva, A.; Chernyaeva, E.; Ivanov, R.; Nasonov, E.; Knyazeva, L.
Abstract : Background: BCD-020 is the first Russian rituximab (RTX) biosimilar which was approved for medical use in lymphoma patients in Russia and some CIS countries. Previous preclinical and clinical studies showed that BCD-020 is highly similar to innovator RTX. Since there are several differences in mechanism of action of RTX in NHL and RA it is recommended to conduct separate clinical studies in oncology and autoimmune indications to prove similar efficacy and safety of biosimilar and original medicine. Objectives: The primary objective was to evaluate the efficacy and safety of BCD-020 used in combination with MTX in patients with RA with inadequate response or intolerance to other DMARDs including 1 or more TNF inhibitor. The secondary objectives included direct comparison of safety, efficacy, pharmacokinetics, pharmacodynamics and immunogenicity of RTX biosimilar and innovator RTX. Methods: This international multicenter randomized double-blind phase 3 clinical study was conducted in patients with active RA despite DMARD therapy, which included 1 or more TNF inhibitor. After completion of screening all eligible patients were stratified by age (<40 years/40 years), ACCPA positive/ACCPA negative, presence/absence of the need for oral steroids. Then patients were randomized in 1:1 ratio into 2 arms: patients from the main arm received BCD-020 1000 mg as an IV infusion on day 1 and day15, patients from the reference arm received innovator RTX by the same regimen. In this work results of the first 6-months period of observation are presented. Results: A total of 160 patients were enrolled; 159 patients had data eligible for efficacy analysis. ACR20 at Week 24 was reported in 84.14% patients in BCD-020 arm and 87.01% in reference arm. The 95% CI for the difference in proportion of ACR20 between groups was [-13.95; 8.74%], where the limits of 95% CI lie within the pre-specified equivalence margin. Both drugs caused deep and sustained depletion of B-cells from peripheral blood without any toxicity to other cell populations. Favorable safety profiles were demonstrated in both groups without any significant differences: AEs have been reported in 59.34% patients from BCD-020 arm and 54.12% patients from reference arm. Treatment discontinuation caused by AE/SAE was reported only for 3 (3.30%) patients in BCD-020 arm and 4 (3.53%) patients in the reference arm (p=1.00). SAEs occurred only in the reference group (2.35%). Binding antibodies were revealed in 3 patients from BCD-020 arm and in 7 patients from reference arm (p=0.209). There were 2 events of neutralizing antibodies against RTX, both in the reference arm (p=0.232). Conclusions: Equivalent efficacy of BCD-020 compared to innovator RTX in patients with active RA has been confirmed. Further clinical evaluation of BCD-020 is planned to confirm long-term efficacy and safety. References: interim study report. Disclosure of Interest: A. Eremeeva Employee of: CJSC BIOCAD, E. Chernyaeva Employee of: CJSC BIOCAD, R. Ivanov Employee of: CJSC BIOCAD, E. Nasonov: None declared, L. Knyazeva: None declared